Rozwój i doskonalenie teorii nauczania i uczenia się literatury = Development and Perfection of the Theory of Teaching and Learning Literature - Pasterniak, Wojciech (1935-2018) (Zielona Góra: Lubuskie Towarzystwo Naukowe)
The paper has methodological character and is dedicated to the development of the conception and theory of teaching and learning literature in a synchronic and diachronical formulation. The author adopts the following assumptions:
Keywords: dydaktyka literatury